22‐2: Enhanced Orthogonality of Inkjet‐Printed OLEDs' Emitting Layer by Novel Ink Composition for Electron Transport Layer. Issue 1 (28th June 2021) - Kang, Taeheon; Gyu Kim, Heung; Ran Mun, Hye; Lee, Juyon; Kim, Sehun; Ha, Jaekook
Abstract : Inkjet printing of OLEDs (Organic Light‐Emitting Diodes) is a revolutionary technology aimed at large‐size panel production, high OLED material consumption efficiency and lower manufacturing costs. Here we report a novel ink composition for ETL which enables uniform ETL formation with full orthogonality to small‐molecule EML material.